A mixed active and passive GLR test for a Fault Tolerant Control System - Jamouli, Hicham; El Hail, Mohamed Amine; Sauter, Dominique (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents an adaptive Generalized Likelihood Ratio (GLR) test for multiple Faults Detection and Isolation (FDI) in stochastic linear dynamic systems. Based on the work of Willsky and Jones (1976), we propose a modified generalized likelihood ratio test, allowing detection, isolation and estimation of multiple sequential faults. Our contribution aims to maximise the good decision rate of fault detection using another updating strategy. This is based on a reference model updated on-line after each detection and isolation of one fault.
Keywords: generalized likelihood ratio; sequential jumps detection; two-stage Kalman filter; fault-tolerant control system